2011
DOI: 10.4103/0970-9371.76943
|View full text |Cite
|
Sign up to set email alerts
|

Guided fine needle aspiration cytology of retroperitoneal masses - Our experience

Abstract: Background:Early pathological classification of retroperitoneal masses is important for pin-point diagnosis and timely management.Aims:This study was done to evaluate the usefulness and drawbacks of guided fine needle aspiration cytology (FNAC) of retroperitoneal masses covering a period of two years with an intention to distinguish between neoplastic and non-neoplastic lesions and to correlate with histologic findings.Materials and Methods:FNAC was done under radiological guidance in all cases using long need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 5 publications
12
23
1
Order By: Relevance
“…The most common nonneoplastic lesion was tubercular lymphadenitis ( n = 12; 42.85%), which is similar to the findings of Ahmad et al [5] ( n = 12; 60%), Mangal et al[1] ( n = 6 cases; 22%), and Gangopadhyay et al [3] ( n = 7; 13.72%).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The most common nonneoplastic lesion was tubercular lymphadenitis ( n = 12; 42.85%), which is similar to the findings of Ahmad et al [5] ( n = 12; 60%), Mangal et al[1] ( n = 6 cases; 22%), and Gangopadhyay et al [3] ( n = 7; 13.72%).…”
Section: Discussionsupporting
confidence: 80%
“…In the current study, most retroperitoneal masses were malignant ( n = 274; 88.4%), which is similar to the findings of Gangopadhyay et al [3]. They reported 7 cases (13.72%) as benign and nonneoplastic and 44 cases (86.27%) as malignant lesions, and Mehdi et al [4] reported 11 cases (28.94%) as benign and nonneoplastic and 27 cases (71.05%) as malignant.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In our institution, we prefer to stain smeared slides (80%) with the Romanowsky stain (Diff-Quik) if a hematopoietic lineage is determined at the time of ROSE. However, the distinction may not always be straightforward [43,44]. Lymphoma cells may artificially show ‘pseudocohesion', especially in highly cellular specimens, and some poorly differentiated nonlymphoid malignancy may show a predominant pattern of dispersion.…”
Section: Fna Diagnosis Of Deep-seated Lymphomas Via Eus/ebus Emphasimentioning
confidence: 99%